Speech intonation in Persian declarative sentences - Maryam Nikravesh; Mahshid Aghajanzade (Vesnu Publications, 2011)
Introduction: Considered as an important factor in communication, prosody is composed of a number of features including intonation, pitch, stress, rhythm and duration, among others. Intonation is the variation of pitch in the course of producing a sentence. In this study, fundamental frequency range was defined as the minimum and maximum amounts of fundamental frequency one can produce when speaking a sentence. The aim of the present study was to evaluate two aspects of prosody, namely, fundamental frequency range and intonation contour in declarative sentences expressed by normal Farsi-speaking adults through laboratory procedures. Materials and Methods: Participants of this cross-sectional descriptive-analytic study were 134 males and females, aging between 18 to 30 years, who natively spoke Farsi. Voice samples obtained by having each subject produce 2 declarative sentences were analyzed by Dr. Speech program (real analysis software). Data were statistically analyzed via unilateral analysis variance and intonation contour was drawn for each of these sentences. Results: The intonation contour was similar among two sex groups. However, fundamental frequency range of males during speaking the sentences significantly differed from that produced by female subjects (P ≤ 0.001). Conclusion: The intonation contour of declarative sentences was characterized by a falling status at the end of the sentence. Females showed much more changes in fundamental frequency in order to transfer declarative state in their expressions than males did. Keywords: Prosody, Intonation contour, Fundamental frequency range, Declarative sentences